Pesan dalam Film “Daring” Karya Mahasiswa Prodi KPI Angkatan 2018-2020 Fakultas Ushuluddin dan Dakwah IAIN Madura: (Analisis Semiotika Ferdinand De Saussure) - Syafyarini, Rini; Amalia Syahidah, Jihan (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2023)
This research discusses the film entitled "Daring" which is a film created by KPI study program students that displays social realities in everyday life. The ability of a film to convey a message that aims to provide education to the audience who watch it makes this online film one of the films that attempt to provide a moral message, education, and social criticism of the surrounding situation which is then packaged into an epic show. This research uses a qualitative approach with Ferdinand De Saussure's semiotic analysis. The results obtained in this research are that there are 12 signifiers and 12 signifiers in the Daring film which consist of moral messages, social messages, and educational messages. Firstly, the moral message conveyed is to speak noble words to parents, be filial to parents, do not miss prayers, do not lie to parents, pray for children, be grateful, and surrender to Allah. Second, the social message conveyed is parental sacrifice, not avoiding responsibility, working together, and maintaining good relationships with friends. Third, the educational message conveyed is that students still want to study well no matter what the circumstances.